CTCF regulates hepatitis B virus cccDNA chromatin topology - Dobrica, MO; Varghese, CS; Harris, JM; Ferguson, J; Magri, A; Arnold, R; Várnai, C; Parish, JL; McKeating, JA (2023)
Hepatitis B Virus (HBV) is a small DNA virus that replicates via an episomal covalently closed circular DNA (cccDNA) that serves as the transcriptional template for viral mRNAs. The host protein, CCCTC-binding factor (CTCF), is a key regulator of cellular transcription by maintaining epigenetic boundaries, nucleosome phasing, stabilisation of long-range chromatin loops and directing alternative exon splicing. We previously reported that CTCF binds two conserved motifs within Enhancer I of the HBV genome and represses viral transcripts, however, the underlying mechanisms were not identified. We show that CTCF depletion in cells harbouring cccDNA-like HBV molecules and in de novo infected cells resulted in an increase in spliced transcripts, which was most notable in the abundant SP1 spliced transcript. In contrast, depletion of CTCF in cell lines with integrated HBV DNA had no effect on the abundance of viral transcripts and in line with this observation there was limited evidence for CTCF binding to viral integrants, suggesting that CTCF-regulation of HBV transcription is specific to episomal cccDNA. Analysis of HBV chromatin topology by Assay for Transposase Accessibility/sequencing (ATAC-Seq) revealed an accessible region spanning Enhancers I and II and the basal core promoter (BCP). Mutating the CTCF binding sites within Enhancer I resulted in a dramatic rearrangement of chromatin accessibility where the open chromatin region was no longer detected, indicating loss of the phased nucleosome up- and down-stream of the HBV enhancer/BCP. These data demonstrate that CTCF functions to regulate HBV chromatin conformation and nucleosomal positioning in episomal maintained cccDNA, which has important consequences for HBV transcription regulation.